(3GdZQjHjfs - (3CMeO Hf eMeO Hf YHO GdQMef GdHGTGfj GdgQhj, CHh YHjO, J (B401 (3g` s
(3ChdgG (B:s
(3cJGH GdUGO HSe Gddg GdQMef GdQMje HGH GdUGO eY GdgeRI hai GdMOjK Cf YHjO Gddg Hf LMT cGf CSde Ke EQJO hJfUQ hGdYjGX HGddg s
(3BNQgG (B:s
(3jfJgi HHGH GdjGA hGdgGA hai GdMOjK cGf Udi Gddg Ydjg hSde jJYhP ef GdCjgejf GdSjd hGdMQjb hGdCjge GdHdO GdPi dGYde Hg BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3GdfUa GdKGfi ef HGH GdUGO eY GdHGAs
(3YdjgG bQGAGJ SfI (B504 (3g`s
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210s
Keywords: (3GdMOjK h GdeUWdMs